Analisis Efektivitas Penggunaan Video Content Sebagai Media Promosi pada Perusahaan PT. Inovasi Teknologi Solusindo (Trustmedis) - Reza Amalia Melindasari; Reiga Ritomiea Ariescy (Universitas Muhammadiyah Surabaya, 2024)
This study aims to analyze the effectiveness of using video content as a promotional media at PT. Inovasi Teknologi Solusindo (Trustmedis), a company engaged in the technology sector with Electronic Medical Records (EMR) as its main product. Along with the rapid development of technology and social media, companies are utilizing platforms such as Instagram and TikTok to reach a wider audience and increase product awareness. This study uses a qualitative case study method with an observational approach during the MBKM program in August-December 2024. Data was collected through social media analytics and Customer Relationship Management (CRM) to assess the effectiveness of video content. The results of the study show that the use of video content, especially through Instagram Reels and TikTok, has proven to be more effective in attracting audience attention compared to text or image posts. Video content that combines educational, entertainment, and promotional elements can increase reach, engagement, and build consumer trust in the products being promoted. In addition, the application of Call to Action (CTA) in videos also contributes to increased interaction and product sales. This study concludes that video content is an effective promotional strategy for PT. Inovasi Teknologi Solusindo in introducing Electronic Medical Records (EMR) products and building stronger relationships with consumers through social media.